Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Leopards on the edge: Assessing population status, habitat use, and threats in Southeast Asia - S. Rostro-García; J.F. Kamler; R. Sollmann; G. Balme; R. Sukmasuang; A. Godfrey; S. Saosoong; K. Siripattaranukul; S. Suksavate; W. Thomas; R. Crouthers; V. In; et al. (Biological Conservation, 2024)

Green aluminum metal-organic frameworks (Al-MOFs) supported on commercial activated carbon for enhanced removal performances of industrial fluoride pollutants - U.T. Uthappa; Kanalli V. Ajeya; Veeman Sannasi; Sang Goo Lee; Eun-Ho Sohn; Bong-Jun Chang; In-Jun Park; Ju Hyeon Kim; Mahaveer D. Kurkuri; Ho-Young Jung (Journal of Water Process Engineering, 2024)

Corrigendum to “Status, supply chain, challenges, and opportunities to advance oyster aquaculture in northern Vietnam” [Aquaculture Volume 572, July 2023] - Sarah C. Ugalde; Sang V. Vu; Cao Truong Giang; Nguyen Thi Hong Ngoc; Thi Kim Anh Tran; John D. Mullen; Vu Van In; Wayne O'Connor (Aquaculture, 2024)

Historical review and contribution to the knowledge of Amythas membranifera (Ampharetidae): an integrative perspective of an Antarctic polychaete - Orlemir Carrerette; Mônica A. V. Petti; Dong-U. Kim; Sandra Bromberg; Gilberto Bergamo; Paulo Y. G. Sumida; In-Young Ahn (Polar Biology, 2023)

Status, supply chain, challenges, and opportunities to advance oyster aquaculture in northern Vietnam - Sarah C. Ugalde; Sang V. Vu; Cao Truong Giang; Nguyen Thi Hong Ngoc; Thi Kim Anh Tran; John D. Mullen; Vu Van In; Wayne O'Connor (Aquaculture, 2023)

In Vitro Study of the Expression of CD1, CD14, CD25, CD30, CD35, CD95 Receptors by Macrophages of Mice Infected with Mycobacterium tuberculosis - D. A. Il’in; V. A. Shkurupy; E. S. Akhramenko (Bulletin of Experimental Biology and Medicine, 2021)

Textile-based cyanobacteria biocomposites for potential environmental remediation applications - Rachel Hart; Pichaya In-na; Maxim V. Kapralov; Jonathan G.M. Lee; Gary S. Caldwell (Journal of Applied Phycology, 2021)
Microalgae and cyanobacteria are effective platforms for environmental remediation (phycoremediation), particularly of air and water. There is limited scope to deploy suspension cultures due to space, cost and maintenance challenges—driving an imperative towards biofilm-based treatment systems; however, these systems are ill-equipped for rapid and mobile deployment. In this study we explored the main technical challenges to developing cheap, accessible and low-maintenance engineered biofilm systems (biocomposites) comprising cyanobacteria ( Synechococcus elongatus ) immobilised to a range of textiles ( n = 4) by natural or synthetic latex binders ( n = 16), chitosan or shellac. Biocomposite viability (measured as net CO 2 uptake) was assessed over 20 days in semi-batch trials. No maintenance was required during this period as the humidity within the reactor was sufficient to support metabolism. Two commercial natural latex binders (AURO 320 and 321) supported strong growth within the biocomposite, outperforming suspension controls. There was variation in textiles performance, with an 80/20 polyester-cotton blend performing most consistently. Biocomposite formulation was varied in terms of binder solids content and cell loading rate, with 5% solids and 2.5% cell loading the most effective combination. We demonstrate the technical feasibility of fabricating functional textile-based cyanobacteria biocomposites and discuss this within the context of developing decentralised wastewater treatment services.

The Effect of Low-Molecular-Weight Allosteric Agonist of Luteinizing Hormone Receptor on Functional State of the Testes in Aging and Diabetic Rats - K. V. Derkach; I. V. Romanova; A. A. Bakhtyukov; I. Yu. Morina; D. V. Dar’in; V. N. Sorokoumov; A. O. Shpakov (Bulletin of Experimental Biology and Medicine, 2021)

The In Vitro M1/M2 Polarization of Macrophages of BCG-Infected Mice - D. A. Il’in; V. A. Shkurupy (Bulletin of Experimental Biology and Medicine, 2020)

Antimicrobial Activity of Biosynthesized Silver Nanoparticles Decorated Silica Nanoparticles - Sachin V. Otari; Sanjay K. S. Patel; Vipin C. Kalia; In-Won Kim; Jung-Kul Lee (Indian Journal of Microbiology, 2019)

In Vitro Analysis of the Expression of CD11, CD29, CD36, and DC-STAMP Molecules during the Formation of Multinuclear Macrophages in BCG-Infected Mice - D. A. Il’in; V. A. Shkurupy (Bulletin of Experimental Biology and Medicine, 2019)

Copper Ferrite Magnetic Nanoparticles for the Immobilization of Enzyme - Sachin V. Otari; Sanjay K. S. Patel; Sang-Yong Kim; Jung Rim Haw; Vipin C. Kalia; In-Won Kim; Jung-Kul Lee (Indian Journal of Microbiology, 2019)

The obligate alkalophilic soda‐lake fungus Sodiomyces alkalinus has shifted to a protein diet - Alexey A. Grum‐Grzhimaylo; Daniel L. Falkoski; Joost van den Heuvel; Claudio A. Valero‐Jiménez; Byoungnam Min; In‐Geol Choi; Anna Lipzen; Chris G. Daum; Duur K. Aanen; Adrian Tsang; Bernard Henrissat; Elena N. Bilanenko; et al. (Molecular Ecology, 2018)
Sodiomyces alkalinus is one of the very few alkalophilic fungi, adapted to grow optimally at high pH . It is widely distributed at the plant‐deprived edges of extremely alkaline lakes and locally abundant. We sequenced the genome of S. alkalinus and reconstructed evolution of catabolic enzymes, using a phylogenomic comparison. We found that the genome of S. alkalinus is larger, but its predicted proteome is smaller and heavily depleted of both plant‐degrading enzymes and proteinases, when compared to its closest plant‐pathogenic relatives. Interestingly, despite overall losses, S. alkalinus has retained many proteinases families and acquired bacterial cell wall‐degrading enzymes, some of them via horizontal gene transfer from bacteria. This fungus has very potent proteolytic activity at high pH values, but slowly induced low activity of cellulases and hemicellulases. Our experimental and in silico data suggest that plant biomass, a common food source for most fungi, is not a preferred substrate for S. alkalinus in its natural environment. We conclude that the fungus has abandoned the ancestral plant‐based diet and has become specialized in a more protein‐rich food, abundantly available in soda lakes in the form of prokaryotes and small crustaceans.

Expression of Pro- and Antiapoptotic Factors in Multinuclear Macrophages of BCG-Infected Mice In Vitro - D. A. Il’in; V. A. Shkurupy (Bulletin of Experimental Biology and Medicine, 2018)

Halobacterium salinarum storage and rehydration after spray drying and optimization of the processes for preservation of carotenoids - Sergei V. Kalenov; Mariia G. Gordienko; Ekaterina D. Murzina; Daniil Y. Poberezhniy; Dmitry V. Baurin; Natalia E. Suzina; Alexander N. Morozov; Liubov M. Yakubovich; Alexey A. Belov; Victor I. Panfilov; Oksana V. Yarovaya; Michail M. Il’in; et al. (Extremophiles, 2018)

Analysis of IL-1α, bFGF, TGF-β1, IFNγ, MMP-1, and CatD Expression in Multinuclea Macrophages In Vitro - D. A. Il’in; S. A. Arkhipov; V. A. Shkurupy (Bulletin of Experimental Biology and Medicine, 2018)

In Vitro Study of Cytophysiological Characteristics of Multinuclear Macrophages from Intact and BCG-Infected Mice - D. A. Il’in; S. A. Arkhipov; V. A. Shkurupy (Bulletin of Experimental Biology and Medicine, 2016)

Expression of CPI-17 in smooth muscle during embryonic development and in neointimal lesion formation - Jee In Kim; Garbo D. Young; Li Jin; Avril V. Somlyo; Masumi Eto (Histochemistry and Cell Biology, 2009)

Polaribacter butkevichii sp. nov., a Novel Marine Mesophilic Bacterium of the Family Flavobacteriaceae - Olga I. Nedashkovskaya; Seung Bum Kim; Anatoly M. Lysenko; Nataliya I. Kalinovskaya; Valery V. Mikhailov; In Seop Kim; Kyung Sook Bae (Current Microbiology, 2005)

Monitoring of the Myoplegical Component of General Anesthesia - V. I. Sud'in (Biomedical Engineering, 2005)

Repeated trans-Arctic invasions in littoral bivalves: molecular zoogeography of the Macoma balthica complex - R. Vinl (Marine Biology, 2003)

Phylogeography of Cerastoderma glaucum (Bivalvia: Cardiidae) across Europe: a major break in the Eastern Mediterranean - R. Nikula; R. Vinl (Marine Biology, 2003)

Human spontaneous laryngeal carcinoma HEp-2 cells are chronically infected with SRV-1 virus, a variant of simian type D retrovirus - L. R. Imamova; Yu. G. Kzhyshkowska; A. S. Ostashkin; A. V. Itkes; K. V. Il'in (Bulletin of Experimental Biology and Medicine, 2000)

The Mechanism of Reactive NO3 Uptake on Dry NaX (X=Cl, Br) - Mikhail Yu. Gershenzon; Sergeid. Il'in; Nikolai G. Fedotov; Yulii M. Gershenzon; Elena V. Aparina; Vladislav V. Zelenov (Journal of Atmospheric Chemistry, 1999)

Selection of the optimal point of intersection of radiation beams as a part of X-ray therapy planning - L. Ya. Klepper; V. I. Il’in (Biomedical Engineering, 1998)

Assessment of tolerance doses of multifractionated irradiation of lungs using the ellis and LQ models - V. I. Il'in; L. Ya. Klepper (Biomedical Engineering, 1998)